ANALISIS PENGARUH DANA PERIMBANGAN TERHADAP KETIMPANGAN PEMBANGUNAN MELALUI PERTUMBUHAN EKONOMI DI KABUPATEN MIMIKA - Ridwan Ridwan (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to determine the effect of balancing funds on development inequality through economic growth in Mimika Regency. This study uses an associative method, the data analysis tool in this study uses path analysis and uses the Eviews application. The results of the study indicate that balancing funds (X) have a simultaneous effect on economic growth (Y1), Revenue Sharing Funds (X1) and General Allocation Funds (X2) have a significant effect individually on economic growth (Y1), Special Allocation Funds (X3) do not have a significant effect individually on economic growth (Y1). The second result of the study obtained no statistically significant relationship between economic growth (Y1) and development inequality (Y2) either individually or simultaneously. The third result of balancing funds (X) does not have an indirect effect on development inequality (Y2) through economic growth (Y1) in Mimika Regency.